Italy : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
This 2004 Article IV Consultation highlights that a cyclical recovery is under way for Italy, with real GDP having risen by 1.2 percent in the first three quarters of 2004 relative to the same period of the previous year, thanks to the favorable external environment and a recovery of investment. A package of corrective measures adopted in mid-2004 is likely to have proven sufficient to keep the fiscal deficit just below 3 percent of GDP last year. IMF staff forecasts growth of 1.5 percent in 2004 and 1.7 percent in 2005.